A randomized, multinational, noninferiority, phase III trial to evaluate the safety and efficacy of BF‐200 aminolaevulinic acid gel vs. methyl aminolaevulinate cream in the treatment of nonaggressive basal cell carcinoma with photodynamic therapy. (1st August 2018) - Morton, C.A.; Dominicus, R.; Radny, P.; Dirschka, T.; Hauschild, A.; Reinhold, U.; Aschoff, R.; Ulrich, M.; Keohane, S.; Ekanayake‐Bohlig, S.; Ibbotson, S.; Ostendorf, R.; et al.
Summary: Background: Basal cell carcinoma (BCC) represents the most common nonmelanoma skin cancer worldwide, affecting mainly adult, fair‐skinned individuals. The World Health Organization distinguishes aggressive and nonaggressive forms, of which prototypical variants of the latter are primary nodular and superficial BCC. Objectives: To demonstrate noninferiority of BF‐200 ALA (a nanoemulsion gel containing 5‐aminolaevulinic acid) compared with MAL (a cream containing methyl aminolaevulinate) in the treatment of nonaggressive BCC with photodynamic therapy (PDT). Noninferiority of the primary efficacy variable (overall patient complete response 12 weeks after last PDT) would be declared if the mean response for BF‐200 ALA was no worse than that for MAL, within a statistical margin of Δ = −15%. Methods: The study was a randomized, phase III trial performed in Germany and the U.K. with ongoing 5‐year follow‐up. Of 281 randomized patients, 138 were treated with BF‐200 ALA and 143 with MAL. Patients received two PDT sessions 1 week apart. Remaining lesions 12 weeks after the second PDT were retreated. Illumination was performed with a red light source (635 nm, 37 J cm −2 ). The results shown include clinical end points and patients' reassessment 12 months after the last PDT. The study was registered with EudraCT (number 2013‐003241‐42). Results: Of the BF‐200 ALA‐treated patients, 93·4% were complete responders compared with 91·8% in the MAL group. The difference of means was 1·6, with a one‐sided 97·5% confidence interval of −6·5, establishing noninferiority ( P < 0·0001). The results for secondary efficacy parameters were in line with the primary outcome. Recurrence rates 12 months after the last treatment were ≤ 10%. Conclusions: Treatment of nonaggressive BCC with BF‐200 ALA‐PDT is highly effective and well tolerated with proven noninferiority to MAL‐PDT. It demonstrates low recurrence rates after 1 year of follow‐up.